VD_FINDINFO Décision / 2013 / 856 vom 15. Oktober 2013 - VD Tribunal cantonal (2013)
DÉTENTION PRÉVENTIVE, DROIT D'ÊTRE ENTENDU, PRINCIPE DE LA CÉLÉRITÉ | 222 CPP (CH), 225 al. 5 CPP (CH), 227 CPP (CH), 228 al. 4 CPP (CH), 393 al. 1 let. c CPP (CH), 393 CPP (CH), 396 CPP (CH), 428 al. 1 CPP (CH), 429 al. 1 let. a CPP (CH), 5 CPP (CH)